The state right to defend its sovereignty in Islam in international law - Rabie, Ziad M. (Opción, 2019)
Research included the concept of the State in international law, in order to know the position of Islamic Law of this concept through descriptive and analytical method by studying the articles and comparative analyzing of them. We discussed the concept of the State’s right to life in Islam. We dealt with the concept of people’s right to life in Islamic Shari’a, and Islamic philosophy in ensuring the human right to life. The research indicates the right of States to use armed force, to protect its people, the political and legal system, from any aggression being attacked by other states.